Investigasi Kepuasan Pelanggan dan Kualitas Pelayanan Menggunakan Metode Servqual dan Kano - Muhammad Candra Nugraha (Universitas Putra Indonesia YPTK Padang, 2022)
The purpose of this study was to determine the level of customer satisfaction of a coffee business in Padang, West Sumatra. The method used is Servqual and the measurement of service quality is the Kano method. This study explores the quality of service that has an impact on customer satisfaction at a coffee business in Padang. The type of data in this study is primary data in the form of a questionnaire that has been distributed to respondents. The number of samples in the study amounted to 100 respondents. The results of the study show that0 with the Servqual method, it is found that the gap scores for 27 service attributes measured in this study produce a negative value, and 1 service attribute produces a positive value. There are 24 one-dimensional attribute categories, which means that consumer satisfaction is proportional to the performance of the attributes. The higher the attribute performance, the higher the customer satisfaction. And 3 attributes of the reverse category, which means the degree of customer satisfaction is higher if the service does not exist.